KAJIAN YURIDIS TERHADAP JUMLAH PERSENTASE KEPEMILIKAN SAHAM DALAM PERSEROAN TERBATAS (Tinjauan atas Undang – Undang no 40 tahun 2007 tentang Perseroan Terbatas) - Muhammad Hatta BJ (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract The Company was founded by two (2) or more persons with a notary deed made ​​in Indonesian , it is as stated in article 7 paragraph 1 of the law No. 40 of 2007. The article mentions that a limited liability company may be established by 2 (two) people, but there are no more rules regarding its ownership , thus allowing the ownership of the same number of shares in a limited liability company that only has two shareholders . With these provisions are void because the law does not regulate the exact number of shareholders and the number of shares in a limited liability company . This resulted in the absence of the majority shareholder and minority shareholder in the company , whereas in the decision- making within a General Meeting of Shareholders , which if it can not be taken by consensus decision , the decision will be taken to be accepted by the majority . Thus , it appears the problem of